Trees for Tomorrow: raising environmental awareness in Jamaica - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Susie Latham explains how the Jamaican Forestry Department has adopted a wide range of ICTs to restore the island´s forests.